(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article is devoted to the analysis of the phenomenon of gradualism in linguistics, as well as the analysis of the phenomenon of gradualism at the text level. When studying a text, it is said that it should be distinguished from a phrase and a sentence, and that the text also has its own category and laws. The importance of considering the phenomenon of gradualness at the level of the text is that the content of gradualism is more understood in a compound sentence and text than in a separate word combination, simple sentences. After all, the phenomenon of gradualness has the characteristic of being manifested in an emotional, quantitative and logical form.